The Role of Local Government in Increasing Young Voter Participation in the 2024 Regional Head Elections - Damay Rusli (Jurnal Multidisiplin Sahombu, 2025)
Young voters have great potential to determine the direction of regional policies, but often show low levels of participation due to various factors, such as lack of information, political apathy, and minimal involvement in the democratic process. This study aims to analyze the role of local governments in increasing young voter participation in the 2024 Regional Head Elections (Pilkada). This study uses a qualitative approach with descriptive methods to examine local government strategies and policies in educating and motivating young voters. Data were collected through interviews, document studies, and observations of relevant government programs. The results of the study show that young voters play an important role in the 2024 Regional Head Elections (Pilkada), with high enthusiasm even though their political decisions are often influenced by external factors such as the social environment, mass media , and peers. The lack of political experience makes them vulnerable to unverified information and emotional campaigns. Therefore, the Regional Government needs to increase the participation of young voters by providing intensive political education, disseminating accurate information, and involving them directly in the election process through cooperation with schools, universities, and youth figures. To overcome apathy, it is also important for the Regional Government to ensure that the 2024 Pilkada is carried out with transparency and fairness, so that young voters can make wiser decisions and actively participate in determining quality future leaders